Small and Medium Sized Manufacturing Companies in Brazil: Is Innovativeness a Key Competitive Capability to Develop? - Thí¼rer, Matthias; Godinho Filho, Moacir; Stevenson, Mark; Fredendall, Lawrence (Acta Scientiarum. Technology, 2015)
Small and medium sized manufacturing companies are important both to economic growth and to supply chains. Yet only limited research has focused on this type of organization - this includes in the area of manufacturing strategy. Using a large scale survey of 149 firms across three States in Brazil, this paper examines the competitive capabilities of small and medium sized manufacturing companies; and the link between their capabilities and performance. Our results show that the best-performing firms are those that lead on capabilities like quality and innovativeness rather than on cost. Much of the available literature on manufacturing strategy emphasizes only four key competitive priorities: cost, flexibility, quality and delivery. Consequently, our results confirm innovativeness as an important, fifth capability for small and medium sized firms in Brazil to maintain or develop. The findings are of relevance both to small and medium sized manufacturing companies in emerging economies and to international firms looking to relocate or outsource to Brazil. Â 